Islamic Reform in Malaya: The Contribution of Shaykh Tahir Jalaluddin - Zakariya, Hafiz (IIUM Press, 2005)
Reformation of religion does not entail changing the very teaching of Islam or the introduction of un-Islamic elements into Islam. Rather reformation of religion is a return to the original sources of Islam as practiced during the period of the Prophet (SAS) and early generations of Muslims, unadulterated by the practices and beliefs that contravened Islam. This salafi reformist discourse, as the historical evidence shows, was adopted by Shaykh Tahir in his attempts to reform Islam in colonial Malaya.